Evaluation of radiographic and metabolic changes in bone metastases in response to systemic therapy with (18)FDG-PET/CT - Gunalp, Bengul (Radiol Oncol, 2015)
BACKGROUND. The aim of the study was to retrospectively evaluate radiographic and metabolic changes in bone metastases in response to systemic therapy with (18)FDG-PET/CT and determine their roles on the evaluation of therapy response. PATIENTS AND METHODS. We retrospectively evaluated radiographic and metabolic characteristics of bone metastases in 30 patients who were referred for the evaluation of response to systemic therapy with (18)FDG-PET/CT. All patients underwent integrated (18)FDG-PET/CT before and after treatment. RESULTS. The baseline radiographic patterns of the target lesions in responders group were lytic, sclerotic, mixed and CT negative; after treatment the radiographic patterns of all target lesions changed to a sclerotic pattern and attenuation increased (p = 0.012) and metabolic activity decreased (p = 0.012). A correlation was found between decreasing metabolic activity and increasing attenuation of the target lesions (r = −0.55) (p = 0.026). However, in nonresponders group, the baseline radiologic patterns of the target lesions were lytic, blastic, mixed and CT negative; after treatment all lytic target lesions remained the same and one CT negative lesion turned to lytic pattern and the attenuation of the target lesions decreased (p ± 0.12) and metabolic activity increased (p = 0.012). A correlation was found between increasing metabolic activity and decreasing attenuation (r = −0.65) (p = 0.032). An exception of this rule was seen in baseline blastic metastases which progressed with increasing in size, metabolic activity and attenuation. CONCLUSIONS. This study shows that the metabolic activity of lesions is a more reliable parameter than the radiographic patterns for the evaluation of therapy response.